Position Estimation Comparison of a 3-D Linear Lateration Algorithm with a Reference Selection Technique - Abdulmalik Shehu Yaro; Ahmad Zuri Sha'ameri; Nidal Kamel (Institute of Advanced Engineering and Science, 2018)
Multilateration system estimates emitter position using time difference of arrival (TDOA) measurement with a lateration algorithm. The position estimation (PE) accuracy of the system depends on several factors such as the number of ground receiving station (GRS)s deployed, the reference station used and the type of lateration algorithm. In this paper, the 3-D PE accuracy of a four-GRS linear lateration algorithm combined with a GRS reference pair selection (GREPS) technique is determined and compared with two different five-GRS linear lateration algorithms. The two five-GRS linear lateration algorithms chosen for comparison are based on single reference total least square (SF-TLS) and multiple reference least square (MF-LS) approaches. Monte Carlo simulation result comparison shows that the four-GRS linear lateration algorithm with the GREPS technique outperformed the SF-TLS and MF-LS with a reduction in horizontal coordinate PE error of about 50% and 30% respectively, and with a 90% reduction in the altitude error